Using MALDI-TOF Mass Spectrometry to Identify Drug Resistant Staphylococcal Isolates from Nonhospital Environments in Brunei Darussalam - Chong, Ko S.; Shazali, Siti A.; Xu, Zhen; Cutler, Ronald R.; Idris, Adi (Interdisciplinary Perspectives on Infectious Diseases, 2016)
Drug resistant bacteria have been a growing threat to the community and hospitals due to the misuse of antibiotics by humans, industrialization, and lack of novel antimicrobials currently available. Little is known about the prevalence of drug resistant bacteria in nonhealthcare environments in Brunei Darussalam and about how antibiotic resistant genes are transferred within these environments. Human contact points from different types of environments in Brunei Darussalam, varying from urban to jungle settings, were swabbed and cultured onto selective media to isolate staphylococci bacteria before performing antimicrobial susceptibility testing on the isolates. The identity of the isolates was determined using MALDI-TOF mass spectrometry (MS). Staphylococci isolates resistant to oxacillin were further tested for their minimum inhibitory concentration (MIC). PCR analysis of the mecA gene, a gene that confers resistance to oxacillin, is done to determine the level of resistance to oxacillin. Ten different staphylococcal species were identified by MALDI-TOF-MS analysis. Out of the 36 staphylococci isolates, 24 were resistant to multiple antibiotics including two isolates which were oxacillin resistant. Some staphylococci isolates had similar antibiotic resistance profiles to other staphylococci isolates of different species in the same location. This work provides the first-ever evidence of drug resistant staphylococci in the nonhospital environment in Brunei Darussalam.